The source code of each crappy thing. Programming, explaining, making, stripping, and digitizing - Saorín, Tomás (Anuario ThinkEPI, 2016)
This article reflects on the concept of source code as it is applied to areas other than computer programming, and relates it to scientific communication, network activism, and micropolitical actions. The usefulness of learning the essential aspects of programming as a universal language and digitizing of objects, buildings, and historical sites in 3D, by digital libraries of cultural heritage, are discussed.
Keywords: Source code; Computer programming; Videotutorials; Social technologies; Maker movement; 3D objects